2018
DOI: 10.1002/ccr3.1556
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of common variable immunodeficiency using embryonic stem cell therapy in a patient with lyme disease: a clinical case report

Abstract: Key Clinical MessageBone marrow transplantation and stem cell therapies have been used for the treatment of common variable immunodeficiency (CVID) and other life‐threatening medical disorders. This is the first known case report in the medical literature describing improvement of both Lyme disease and CVID with human embryonic stem cell therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Immune dysfunction/immune deficiency: This occasionally required subcutaneous or intravenous immunoglobulin therapy (IVIG), as immunoglobulins are necessary to fight infections (CVID), modulate immunity [198], heal (small fiber) neuropathy, POTS, and address autoimmune encephalopathy [199]. Improvement of CVID using embryonic stem cell therapy in Lyme disease may be an option in resistant disease [200]. More than 72% of participants had immune dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Immune dysfunction/immune deficiency: This occasionally required subcutaneous or intravenous immunoglobulin therapy (IVIG), as immunoglobulins are necessary to fight infections (CVID), modulate immunity [198], heal (small fiber) neuropathy, POTS, and address autoimmune encephalopathy [199]. Improvement of CVID using embryonic stem cell therapy in Lyme disease may be an option in resistant disease [200]. More than 72% of participants had immune dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In another case study by Horowitz et al, an 18-year-old male was observed [7]. He had an extensive history, including recurrent infections, Lyme disease, CVID, pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections (PANDAS), and celiac disease [7].…”
Section: Case Studiesmentioning
confidence: 99%
“…In another case study by Horowitz et al, an 18-year-old male was observed [7]. He had an extensive history, including recurrent infections, Lyme disease, CVID, pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections (PANDAS), and celiac disease [7]. He was also suffering from neuropsychiatric disorders, including attention-deficit and hyperactivity disorder (ADHD), likely attributable to heavy metal exposure at school [7].…”
Section: Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations